Differential microbiome features in lake–river systems of Taihu basin in response to water flow disturbance - Xiao, Peng; Wu, Yao; Zuo, Jun; Grossart, Hans-Peter; Sun, Rui; Li, Guoyou; Jiang, Haoran; Cheng, Yao; Wang, Zeshuang; Geng, Ruozhen; Zhang, He; Ma, Zengling; et al. (Frontiers in Microbiology, 2024)
In riverine ecosystems, dynamic interplay between hydrological conditions, such as flow rate, water level, and rainfall, significantly shape the structure and function of bacterial and microeukaryotic communities, with consequences for biogeochemical cycles and ecological stability. Lake Taihu, one of China’s largest freshwater lakes, frequently experiences cyanobacterial blooms primarily driven by nutrient over-enrichment and hydrological changes, posing severe threats to water quality, aquatic life, and surrounding human populations. This study explored how varying water flow disturbances influence microbial diversity and community assembly within the interconnected river-lake systems of the East and South of Lake Taihu (ET&ST). The Taipu River in the ET region accounts for nearly one-third of Lake Taihu’s outflow, while the ST region includes the Changdougang and Xiaomeigang rivers, which act as inflow rivers. These two rivers not only channel water into Lake Taihu but can also cause the backflow of lake water into the rivers, creating distinct river-lake systems subjected to different intensities of water flow disturbances. Utilizing high-throughput sequencing, we analyzed the composition and distributions of microbial communities to compare their diversity and assembly processes across these different hydrological regimes. This study demonstrated that water flow intensity and temperature disturbances significantly influenced diversity, community structure, community assembly, ecological niches, and coexistence networks of bacterial and eukaryotic microbes. In the ET region, where water flow disturbances were stronger, microbial richness significantly increased, and phylogenetic relationships were closer, yet variations in community structure were greater than in the ST region, which experienced milder water flow disturbances. Additionally, migration and dispersal rates of microbes in the ET region, along with the impact of dispersal limitations, were significantly higher than in the ST region. High flow disturbances notably reduced microbial niche width and overlap, decreasing the complexity and stability of microbial coexistence networks. Moreover, path analysis indicated that microeukaryotic communities exhibited a stronger response to water flow disturbances than bacterial communities. Our findings underscore the critical need to consider the effects of hydrological disturbance on microbial diversity, community assembly, and coexistence networks when developing strategies to manage and protect river-lake ecosystems, particularly in efforts to control cyanobacterial blooms in Lake Taihu.